Pengaruh Motivasi Belajar Terhadap Hasil Belajar Siswa Kelas Vii Pada Mata Pelajaran PAI Di SMP-IT Nur Riska Lubukinggau - Anggraini, Sela; Akip, Muhamad; Azman, Zainal (Edification Journal : Pendidikan Agama Islam, 2024)
In this study entitled "The Effect of Learning Motivation on Learning Outcomes of Class VII Students in PAI Subjects at SMP-IT Nur Riska Lubukinggau". The formulation of the problem posed is How Learning Motivation Against Student Learning Outcomes in Class VII SMP-IT Nur Riska Lubuklinggau. What are the Learning Outcomes of Grade VII SMP-IT Nur Riska Lubuklinggau. Is there an influence of learning motivation on student learning outcomes in Islamic religious education subjects at SMP-IT Nur Riska Lubuklinggau. This type of research is a non-experimental quantitative study, taking the background of SMP-IT Nur Riska Lubuklinggau as the sample in this study. Data collection techniques were carried out by observation, interviews, questionnaires, and documentation. Data analysis was carried out by selecting and compiling the data obtained then processed and analyzed so that conclusions could be drawn, first after determining the placement of high, medium and low categories on learning motivation in class VII SMP-IT Nur Riska Lubuklinggau, that the high group consisted of 2 respondents with a percentage of 14.00%, the medium group consisted of 10 respondents with a percentage of 72.00%, while the low group consisted of 2 respondents with a percentage of 14.00%. Second, the high group has the highest percentage, namely 64.00% or about 9 respondents, the middle group has the second percentage, namely 22.00% or about 3 respondents, while the low group occupies the third percentage, namely 14.00% or about 2 respondents. . Thus it can be seen that the student learning outcomes in class VII SMP-IT Nur Riska Lubuklinggau, this means that the alternative hypothesis is accepted while the null hypothesis is rejected, with the result being t count (0.750) > t table (0.532).